THE EFFECT OF RIDDLE GAME ON STUDENTS’ VOCABULARY MASTERY - Wiki Tedi Rahmawati; Yunita Mutiara Harahap; Fitri Wahyuni Sembiring (Pedagogi: Jurnal Ilmiah Pendidikan, 2022)
This research was aimed to find the effect of riddle game on students’ vocabulary mastery. This research was conducted by using experimental research design with two groups namely experimental and control. The population was all the students of grade VIII of SMP Al Washliyah 08 Medan in academic year 2019-2020 which consisted of two classes namely VIII2 and VIII4. The total number of the population was 60 students. Cluster random sampling was applied to decide the sample group. The experimental group was taught by applying Riddle Game whereas the control group was taught without specific strategy. The instrument for collecting the data was multiple choices test consisted of 20 items. After the data has been collected, the data then were analyzed by using t-test formula. Data analysis resulted that tobserved value was higher than ttable value (3.05 > 2.00172) at level of significance 0.05 with degree of freedom (df) = 58. It meant Ha was accepted and Ho was rejected. Thus, the riddle game strategy significantly affected students’ vocabulary mastery.